The Grand Challenge for the Future Vaccines for Poverty-Related Diseases from Bench to Field - Kaufmann, Stefan H.E; Lambert, Paul-Henri (Birkhäuser Advances in Infectious Diseases, 2005)
The most urgently needed vaccines are those against poverty-related diseases such as tuberculosis, malaria and HIV. However, there is a considerable gap between the development of a vaccine and the implementation as a useful measure for disease control. Major obstacles need to be overcome even after successful completion of the preclinical stage. This book provides an important link between vaccine development and application under the particular conditions in developing countries. The editors, S.H.E. Kaufmann and P.H. Lambert - one from the field of basic research and the other an expert on the side of applied vaccinology - have gathered contributions from specialists of both fields in an attempt to create a source of information that has thus far not been available.